Grandmothers as substitute mothers to their preschool aged grandchildren - Suico, Lanore V.
This study aimed to determine the parenting practices of grandmothers to their preschool-aged grandchildren with Overseas Filipino Worker mothers. The influence of age on the performance of parenting practices was also explored in this study. The grandmother-respondents were grouped into the Younger Grandmothers (40 to 52 ears) and Older Grandmothers (43 to 65 years). A checklist and an interview guide were used to gather information. Both qualitative and quantitative methods were employed to gather and analyze data...